Preferensi Konsumen terhadap Pembelian Produk Virgin Coconut Oil (Vco) di Kota Pontianak - Kurniati, Dewi; Anggraysari, Diah; Aritonang, Marisi (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2022)
Community activities have been disrupted because they are facing  the Covid-19 pandemic, which can cause mild infections of the respiratory tract and lead to death. It is great important for the community to maintain a healthy immune system, such as consuming additional supplements of Virgin Coconut Oil. However, the knowledge of most people about VCO products and benefits is still very minimal, because there are many substitute products for herbal health supplements that are easily found by consumers in the online or offline market. The study was carried out in six sub-districts of Pontianak City with 45 respondents who were taken based on accidental sampling and analyzed using the Fishbein Multi-attribute method to identify product attributes and attributtes that are most considered by consumers in purchasing VCO products. The results showed the attributes that became consumer preferences in purchasing VCO products sequentially were the attributes of benefit (19.93), size (19.26), certification (19.05), nutrition (18.87), price (18.86 ), taste (18.75), label (18.56), scent (18.29), and shape (16.90). So therefore attributes of VCO products that are most considered by customers in making purchases are the attributes of benefits (19,93).